CHARACTERISTICS OF VOLCANIC ROCK CIKOTOK FORMATION AT CIHARA AND SURROUNDING AREA, LEBAK DISTRICT, BANTEN PROVINCE - Patonah, Aton; Permana, Haryadi; Alamsyah, Fadhli (Faculty of Geological Engineering, Universitas Padjadjaran, 2020)
Volcanic rock of Cikotok Formation in southern part of the Bayah Dome, known as old andesite volcanic, is one of the parent rocks contain gold and base metal mineralization. This study aims to identify in more detail about texture, structure, and composition of mineral constituents of the rock by using field observation and petrographic methods. The result shows that the volcanic rocks of Cikotok Formation were came from shallow eruptions and relatively rapid cooling characterized by trachytic to porphyritic texture, embayment, and amygdaloidal structure. Most of these rocks have altered. These altered rocks are believed related to deformation at Oligo-Miocene that causing the presence of weak zone so that hydrothermal fluid can passes through